PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI TEAM QUIZ PADA PEMBELAJARAN TEMATIK TEMA 1 SUBTEMA 3 PEMBELAJARAN 1 KONDISI POLITIK NEGARA ASEAN DI KELAS VI MIN 2 SIDOARJO - Septiani, Anik (Journal Of Islamic Elementary School (JIES), 2019)
Improving student learning outcomes needs special attention. This study aims to determine the implementation of the Team Quiz strategy and the improvement of thematic learning outcomes of theme 1 subtheme 3 political conditions in ASEAN countries after using the Team Quiz strategy in class VI-A MIN 2 Sidoarjo. This research is a classroom action research using Kurt Lewin’s model. Research data obtained from interviews, observations, written tests, and non-tests. The results showed: the implementation of the Team Quiz strategy to improve thematic learning outcomes of theme 1 sub-theme 3 political conditions of the Asean country in class VI-A MIN 2 Sidoarjo was carried out well. It is evidenced by the results of the teacher’s activity value increasing from the first cycle of 70 to 86 in the second cycle. The results of student activity scores also increased from the first cycle of 77 to 88 in the second cycle. This can also be proven from student learning outcomes and the percentage of complete learning outcomes in each cycle. In the pre-cycle the class average was 57.59, increased in the first cycle to 78.07, and the second cycle increased again to 88.43. The percentage of completeness of student learning outcomes in the first cycle of 53.57% increased to 82.14% in the second cycle.